Intellectual Developmental Disability Bio-Banking: Public Support from the European Union - Moedas, Carlos (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Supporting health research has been a long-standing commitment for the European Union (EU). Over several Framework Programmes for Research and Innovation, the EU contributed to advancing scientific knowledge on intellectual disability and addressing the unmet needs of affected people, their families and carers. Bio-banking is instrumental to such research. This article presents the various streams through which the EU has helped developments in this area and highlights opportunities for the future.